THE ROLE OF CREATIVITY INNOVATION AND RESILIENCE ON EMPLOYEE PERFORMANCE AT NUSANTARA GARMENT COMPANY SURABAYA - Dela Kusniya; Siti Mujanah (Journal of Applied Management and Business, 2022)
This study aims to analyze the related Creativity, Innovation and Resilience partially or simultaneously on Employee Performance at Nusantara Garment Company Surabaya. The type of research used is quantitative and the sample used is 85 peoples. The data collection method used is a survey method with a questionnaire instrument. The results of this study conclude that the T-test analysis shows that the variables of Creativity, Innovation and Resilience have a significant effect on employee performance.Furthermore, the results of the F test analysis shows that Creativity, Innovation and Resilience as simultaneously have a significant effect on Employee Performance. This indicates that improving employee performance in garment companies can be done by choosing employees who have Creativity, Innovation and Resilience when recruiting, or providing coaching and training to generate creativity, Innovation and Resilience of employees.